ANALISIS KEBUTUHAN (NEED) MAHASISWA TERHADAP PELAYANAN KESEHATAN KAMPUS UNIVERSITAS DIPONEGORO - Lilis Setiyaningrum; Septo Pawelas Arso; Eka Yunila Fatmasari (Jurnal Kesehatan Masyarakat (Undip), 2017)
The availability of health service in college area has important role in achieving college purpose. One of those purposes is fulfill student welfare in improving healthy lifestyle. Based on the results of observations reinforced preliminary study shows that the utilization of Poliklinik Undip by students is still less than optimal. The existence of Poliklinik Undip development plan is required to draft marketing strategy, one of that plans can be called need analysis toward health service. This study aims to describe students need level toward campus health service named Poliklinik Undip. The method used is quantitative method with cross sectional by using 100 respondents of undergraduate students Diponegoro University. The result of research shows that the characteristics of Diponegoro University students are more female (74.0%) than the male, with the most semester status is the old students (70.0%). About 59% students are categorized having low income (from allowance or grants) that is about <Rp1.112.000,- per month and the number of students having health insurance are less. Almost of students (59,0%) have limited knowledge about campus health service Diponegoro University named Poliklinik Undip. Even thought, the number of students need toward health service is categorized high (86,0%). The result shows that the number of need has correlation with status semester variable (Pvalue 0,003), students’ knowledge about health service in Poliklinik Undip (Pvalue 0,001) and students’ sick accidents (Pvalue 0,000). Therefore, students’ characteristics (gender, income and insurance owning) does not indicating any correlation with the number of need. Students’ expect based on Permenkes No. 9 Tahun 2014 tentang Klinik that outpatient health service is as good as Klinik Pratama. Based on that statement, Dipinegoro University needs to develop Poliklinik Undip at least based on student expectation mentioned above.